Tờ trình Dự án Luật sửa đổi, bổ sung một số điều của Luật Đấu giá tài sản (Kèm Tờ trình tóm tắt) - Chính phủ (2023)
Toàn văn Tờ trình Dự án Luật sửa đổi, bổ sung một số điều của Luật Đấu giá tài sản (Kèm Tờ trình tóm tắt).